A retrospective and agenda for future research on Chinese outward foreign direct investment. Issue 1 (January 2018) - Buckley, Peter; Clegg, L; Voss, Hinrich; Cross, Adam; Liu, Xin; Zheng, Ping
Abstract Our original 2007Journal of International Business Studies article, "The determinants of Chinese Outward Foreign Direct Investment", was the first theoretically based empirical analysis of the phenomenon. It utilised internalisation theory to explain the internationalisation of Chinese state-owned enterprises. This paper showed that we had failed to ask sufficiently challenging questions about the effects of home country institutions on outward foreign direct investment (OFDI). This Retrospective builds on the extensive subsequent research to show the importance of context in constructing satisfactory theoretical explanations of OFDI. Building on these foundations, we propose research challenges for the next decade on Chinese OFDI that transcend the Chinese context and have wider theoretical applicability. Examining alternative forms of social and economic organisation allows the creation of special theories of foreign direct investment nested within the general theory. Following such a strategy would enable International Business research to make a contribution across the social sciences. Résumé Notre article original de 2007 publié dansJournal of International Business Studies, "The determinants of Chinese Outward Foreign Direct Investment", a été la première analyse empirique fondée sur une théorie du phénomène. Elle a utilisé la théorie de l'internalisation pour expliquer l'internationalisation des entreprises publiques chinoises. Cet article a montré que nous n'avions pas posé de questions suffisamment difficiles sur les effets des institutions du pays d'origine sur l'investissement direct étranger sortant (IDES). Cette rétrospective s'appuie sur les nombreuses recherches qui ont suivi pour montrer l'importance du contexte dans la construction d'explications théoriques satisfaisantes de l'IDES. S'appuyant sur ces fondations, nous proposons des défis de recherche pour la prochaine décennie sur les IDES chinois qui transcendent le contexte chinois et ont une plus large applicabilité théorique. L'examen de formes alternatives d'organisation sociale et économique permet la création de théories particulières sur l'investissement étranger direct imbriquées dans la théorie générale. Adopter une telle stratégie permettrait à la recherche enInternational Business de faire une contribution au niveau des sciences sociales. Resumen Nuestro artículo publicado originalmente en el 2007 en elJournal of International Business Studies, "Los determinantes de la inversión extranjera directa saliente china", fue el primer análisis empírico basado en teoría del fenómeno. Este usa la teoría de internalización para explicar la internacionalización de las empresas estatales chinas. Este documento demostró que no habíamos formulado preguntas suficientemente retadoras sobre los efectos de las instituciones del país de origen en la inversión extranjera directa saliente (IEDS). Esta Retrospectiva se basa en la extensiva investigación subsecuente para mostrar la importancia del contexto en la construcción de explicaciones teóricas satisfactorias de la IEDS. Sobre la base de estos fundamentos, proponemos retos de investigación para la próxima década sobre la IEDS china que trasciende el contexto chino y que tiene una amplia aplicabilidad teórica. La examinación de formas alternativas de organización social y económica permite la creación de teorías especiales de inversión extranjera directa anidadas en la teoría general. Seguir esta estrategia permitiría a la investigación en Negocios Internacionales hacer contribuciones transversalmente a las ciencias sociales. Resumo Nosso artigo original do Journal of International Business Studies de 2007, "Os determinantes do investimento direto externo chinês para o estrangeiro", foi a primeira análise empírica do fenômeno com base teórica. Ele utilizou a teoria da internalização para explicar a internacionalização das empresas estatais chinesas. Esse artigo mostrou que falhamos em fazer perguntas suficientemente desafiadoras sobre os efeitos das instituições do país de origem sobre o investimento direto externo para o estrangeiro (OFDI). Esta Retrospectiva baseia-se na extensa subsequente pesquisa para mostrar a importância do contexto na construção de explicações teóricas satisfatórias de OFDI. Com base nesses fundamentos, propomos desafios de pesquisa para a próxima década sobre os OFDI chineses que transcendem o contexto chinês e têm maior aplicabilidade teórica. O exame de formas alternativas de organização social e econômica permite a criação de teorias especiais de investimento direto estrangeiro aninhadas na teoria geral. Ao seguir essa estratégia, a pesquisa em negócios internacionais pode fazer uma contribuição para as ciências sociais. 概要 我们最初在2007年发表于《国际商务研究期刊》的文章"中国对外直接投资的决定因素"是对这一现象的第一个基于理论的实证分析。它运用内部化理论来解释中国国有企业的国际化。本文表明, 我们当时并没能就本国制度对对外直接投资(OFDI)的影响提出有足够挑战性的问题。这篇回顾文章建立在广泛的后续研究之上, 以表明在构建令人满意的对外直接投资理论解释中情境的重要性。建于这些基础之上, 我们提出了未来十年中国对外直接投资的研究挑战, 这些挑战超越中国情境, 并具有更广泛的理论适用性。研究社会及经济组织的替代形式可以创建嵌套在通用理论中的外国直接投资的特殊理论。遵循这样的策略将使国际商业研究能够为整个社会科学做出贡献。